Developmentally Regulated Rebound Depolarization Enhances Spike Timing Precision in Auditory Midbrain Neurons - Sun, Hongyu; Zhang, Hui; Ross, Alysia; Wang, Ting Ting; Al-Chami, Aycheh; Wu, Shu Hui (Frontiers in Cellular Neuroscience, 2020)
The inferior colliculus (IC) is an auditory midbrain structure involved in processing biologically important temporal features of sounds. The responses of IC neurons to these temporal features reflect an interaction of synaptic inputs and neuronal biophysical properties. One striking biophysical property of IC neurons is the rebound depolarization produced following membrane hyperpolarization. To understand how the rebound depolarization is involved in spike timing, we made whole-cell patch clamp recordings from IC neurons in brain slices of P9-21 rats. We found that the percentage of rebound neurons was developmentally regulated. The precision of the timing of 1st spike on the rebound increased when the neuron was repetitively injected with depolarizing current following membrane hyperpolarization. The average jitter of the 1st spikes was only 0.5 ms. The selective T-type Ca2+ channel antagonist, mibefradil, significantly increased the jitter of the 1st spike of neurons in response to repetitive depolarization following membrane hyperpolarization. Furthermore, the rebound was potentiated by 1-2 preceding rebounds within a few hundred milliseconds. The 1st spike generated on the potentiated rebound was more precise than that on the non-potentiated rebound. Adding calcium chelator, BAPTA, into the cell, the rebound potentiation no longer occurred and the precision of the 1st spike on the rebound was not improved. These results suggest that the postinhibitory rebound mediated by T-type Ca2+ channel promotes spike timing precision in IC neurons. The rebound potentiation and precise spikes may be induced by increases in intracellular calcium levels.